Screen-based sedentary behavior during adolescence and pulmonary function in a birth cohort - Bruna Gonçalves C. da Silva; Ana M. B. Menezes; Fernando C. Wehrmeister; Fernando C. Barros; Michael Pratt (BMC, 2017)
Abstract Background Adolescents spend many hours in sitting activities as television viewing, video game playing and computer use. The relationship between sedentary behavior and respiratory health remains poorly elucidated. To date there have been no studies evaluating the relationship between sedentary behavior and pulmonary function in young populations. The purpose of this study is to examine the association between the trajectory of screen-based sedentary behavior from 11 to 18 years and pulmonary function at 18 years in a Brazilian birth cohort. Methods Data from a longitudinal prospective study conducted among the participants of the 1993 Pelotas (Brazil) Birth Cohort. Time spent on television, video games, and computers during a weekday was self-reported at ages 11, 15 and 18 years. For each age, sedentary behavior was defined as the sum of time spent on these screen-based activities. To evaluate the sedentary behavior trajectory during adolescence group-based trajectory modeling was used. Outcome variables were three pulmonary function parameters: forced expiratory volume in one second (FEV1), forced vital capacity (FVC), and peak expiratory flow (PEF), evaluated by spirometry, at 18 years expressed as z-scores. Crude and adjusted linear regressions, stratified by sex, were performed. Results The three-group trajectory of sedentary behavior was the best fitting model. The trajectory groups were: always high (representing 38.8% of the individuals), always moderate (54.1%), and always low (7.1%). In the adjusted analyses, boys in the always-low group for sedentary behavior had higher FVC at 18 years (β = 0.177; 95% CI:0.027;0.327; p = 0.021) than boys in the always-high group. There were no differences for other pulmonary function parameters in boys. No significant association was found for girls. Conclusion The trajectory of screen-based sedentary behavior throughout adolescence was not consistent associated with pulmonary function at 18 years.